2022
DOI: 10.1002/acp.3946
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal factors and mental well‐being are associated with accuracy in judging the veracity of political news

Abstract: More work needs to be done to understand how mental well‐being and interpersonal factors are associated with biases in judging the veracity of true and false political information. Three days before the 2020 U.S. presidential election, 477 participants guessed the veracity of true and false political statements. Interpersonal factors (e.g., high prosociality and a need to belong) and mental health risk factors (e.g., high depressive symptoms and low eudaimonic well‐being) were highly associated with believing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 115 publications
(254 reference statements)
0
6
0
Order By: Relevance
“…And, yet, another possibility taps the connection between depression and negative affect (Crawford & Henry, 2004), and negative affect has been shown to correlate with misinformed thinking (Martel et al, 2020; Rauwolf, 2022). This is a notably intriguing possibility insofar as Rauwolf (2022) shows that correlation between depression and, in that case, discernment in judging false statements largely disappears once accounting for negative affect. Clearly, much remains to be done to understand the mechanisms that link depression and conspiracy beliefs and how the moderators we have identified affect those processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And, yet, another possibility taps the connection between depression and negative affect (Crawford & Henry, 2004), and negative affect has been shown to correlate with misinformed thinking (Martel et al, 2020; Rauwolf, 2022). This is a notably intriguing possibility insofar as Rauwolf (2022) shows that correlation between depression and, in that case, discernment in judging false statements largely disappears once accounting for negative affect. Clearly, much remains to be done to understand the mechanisms that link depression and conspiracy beliefs and how the moderators we have identified affect those processes.…”
Section: Discussionmentioning
confidence: 99%
“…To cope with such feelings, individuals often seek to regain a sense of control and conspiracy theories facilitate this process by providing explanations and a sense of certainty (Kossowsak & Bukowski, 2015;Levinsson et al, 2021;Moulding et al, 2016;van Prooijen, 2017;van Prooijen & Douglas, 2017). And, yet, another possibility taps the connection F I G U R E 4 Heterogeneous impact of moderate depressive symptoms, wave 3 between depression and negative affect (Crawford & Henry, 2004), and negative affect has been shown to correlate with misinformed thinking (Martel et al, 2020;Rauwolf, 2022). This is a notably intriguing possibility insofar as Rauwolf (2022) shows that correlation between depression and, in that case, discernment in judging false statements largely disappears once accounting for negative affect.…”
Section: Discussionmentioning
confidence: 99%
“…In our literature review, we found seven papers (Efstratiou and De Cristofaro, 2022;Gaillard et al, 2021;Bryanov and Vziatysheva, 2021;Beauvais, 2022;Tsamakis et al, 2022;Ecker et al, 2022;Baptista and Gradim, 2020) that summarise existing literature regarding the drivers and factors leading to the acceptance, adherence, and belief in fake news. Nine additional papers (Auslander et al, 2017;Pickles et al, 2021;Delmastro and Paciello, 2022;Preston et al, 2021;Xiong et al, 2022;Rauwolf, 2022;Kim and Kim, 2020;Sindermann et al, 2021;Sultan et al, 2022) reported findings from conducted experiments and surveys to study specific psychological and cognitive drivers and processes in this field.2 www.efsa.europa.eu/publications EFSA Supporting publication 2024:EN-8863…”
Section: Believing Fake Newsmentioning
confidence: 99%
“…From a psychological standpoint, Preston et al (2021), Rauwolf (2022), and Delmastro and Paciello ( 2022), all offered insights into the role of emotional factors relating to fake news belief and susceptibility. Preston et al (2021) studied the role of emotional intelligence (EQ) in a sample of U.K. participants, finding that there is a significant positive relationship between EQ and fake news detection ability.…”
Section: Emotional Factors Behind Fake News Belief and Susceptibilitymentioning
confidence: 99%
“…Additionally, some research has suggested that younger adults may be more vulnerable than their older adult counterparts (e.g., Sarno et al, 2020; Sheng et al, 2011). Interestingly, younger age has also been linked to an increased vulnerability to text attacks (Clasen et al, 2021) and younger adults have been reported to believe false information more than older adults (Buchanan, 2020; Rauwolf, 2022; Vijaykumar et al, 2021). However, older adults have been found to share more false information online than any other age group (Allcott & Gentzkow, 2017; Brashier & Schacter, 2020; Schaewitz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%